THE ROLE OF ISLAMIC WINDOWS IN ENHANCING ISLAMIC BANKING: A CASE STUDY OF MEETHAQ WINDOW FOR ISLAMIC BANKING (2013-2022) - Bezaze, Halima (The journal of contemporary issues in business and government, 2024)
This study aims to shed light on one of the advantages of Islamic windows, which is enhancing Islamic banking, through presenting and analyzing the experience of Maethaq Window for Islamic Banking in the Sultanate of Oman during the period (2013-2022). The study concluded that Maethaq Window has contributed to the promotion of Islamic banking by successfully attracting significant Islamic deposits, particularly investment deposits, which constitute 70% of its total deposits. It has diversified its financing formats in the form of Murarabah, musharakah, istisna'a, agency with investment, and ijara ending with ownership .